Event Management Strategy Of Narawandira Temporary Exhibition At Ngayogyakarta Hadiningrat Karaton In 2023 - Yoga Harfa Pangestu; Angga Intueri Mahendra P (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Management strategy is an importantl part of an organization, involving decision-making plans that utilize available resources to achieve the established vision and objectives. This research was conducted due to an interest in the management process of the temporary exhibition "Narawandira" at the Yogyakarta Palace, aiming to achieve success in its organization. The research utilized a qualitative descriptive approach with in-depth interviews and direct observations to obtain comprehensive results and information for the study. The research findings, following Joe Goldblatt's event management process, which consists of research, design, planning, coordination, and evaluation, demonstrate that the event management strategy involving the five-step process has been successfully applied in organizing the "Narawandira" temporary exhibition in 2023 at the Yogyakarta Palace. Through research, design, planning, coordination, and evaluation, the exhibition effectively implemented the event management strategy with the objective of conveying the message about the relationship between humans and nature, as well as presenting reflections on the continuity of nature conservation and changes throughout time.